On the Jurisdictional Powers of the Eurasian Economic Union - NICKOLAEVNA, Malaya Tatiana; FEDOROVICH, Malyy Alexander; IVANOVNA, Nesterova Tatiana (Journal of Advanced Research in Law and Economics, 2017)
At the heart of the regulatory bodies of the Eurasian Economic Union (EEU) we may find organizational elements of the institutions of the European Union (EU). This is understandable, since the EU experience proved to be quite attractive and its application helps to form relevant structures in other international associations. The EU Commission is one of the key institutions. Similar body has been established in the Eurasian Union, though taking into consideration the specificity reflecting the peculiarities of the regulatory bodies in the successor states of the former Soviet Union. The article considers one of the aspects of the EEU Commission, namely jurisdictional function that is a new line in the activity of the executive-administrative body.